The Influence of Quality of Work Life and Job Satisfaction on Employee Performance at the Office of Public Works and Spatial Planning (PUPR) of Seluma Regency - Yuni Widiyanti; Sri Handayani; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Human Resources (HR) is an important resource. For this reason, in order for these human resources to function optimally in an organization, it is necessary to be managed in such a way by the management in order to increase organizational effectiveness. The research objective was to determine the effect of quality of work life and job satisfaction on employee performance at the Office of Public Works and Spatial Planning (PUPR) of Seluma Regency. The sample in this study were all employees who had become State Civil Apparatuses (ASN as many as 52 employees. The sampling method was purposive sampling. The data collection technique was by means of a questionnaire. The analytical method used was multiple regression analysis, hypothesis testing t and hypothesis testing f The multiple regression results have the regression equation Y = 8.360 + 0.328X1 + 0.488 X2, which has a positive regression direction meaning that if the quality of work life and job satisfaction increase, employee performance will also increase.Quality of work life has a significant influence on employee performance at Office of Public Works and Spatial Planning (PUPR) of Seluma Regency.This is evidenced by the results of partial hypothesis testing (t test) that tcount is greater than ttable (3.284 > 1.675) and a significant value of 0.002 is less than 0.05. Job satisfaction has significant influence on employee performance at the Public Works and Spatial Planning (PUPR) Office of Seluma Regency. This is evidenced by the results of partial hypothesis testing (t test) that tcount is greater than ttable (4.490 > 1.675) and a significant value of 0.000 is smaller than 0.05. The quality of work life and job satisfaction have a jointly significant influence on the performance of employees at the Public Works and Spatial Planning (PUPR) Office of Seluma Regency. This is evidenced by the results of simultaneous hypothesis testing (test f) that Fcount > Ftable (26.812 > 3.19) and a significant value of 0.000 is less than 0.05. The value of the coefficient of determination is 0.523. This means that X1 (quality of work life) and X2 (job satisfaction) have a contribution to performance (Y) of 52.3% while the remaining 47.7% is influenced by other variables not examined in this study.